Hubungan Antara Asupan Energi Dan Asupan Protein Dengan Status Gizi Pada Pasien Penyakit Paru Obstruktif Kronik (Prok) Rawat Jalan Di Rumah Sakit Paru Dr. Ario Wirawan Salatiga - Anggraini, Tyas Shinta, Elida Soviana, S.Gz., M.Gizi, dr. Listiana D.S, M.Si (2017)
Introduction: Important factors that affect the course of disease COPD is nutritional status. Pasein COPD tend to have less nutritional status or malnutrition caused by a decrease in food intake, increased energy expenditure and humoral factors. COPD is a non-communicable disease was ranked first out of 10 major diseases in RSPAWan in the last 5 years. Based on preliminary stuji results showed 80% of patients with the nutritional status of patients and 80% of energy and protein intake less category. Objective :The purpose of the study to determine the correlation of energy intake and protein intake with nutritional status in patients with Chronic Obstructive Pulmonary Disease ( COPD ) in the Hospital Outpatient Pulmonary Dr. Ario Wirawan Salatiga. Research Methods:Cross sectional study design .Total sample of 30 subjects selected by consecutive sampling. Nutrient intake data was obtained through interviews using a Food Frequency Semiquantitative and nutritional status data obtained through the measurement of Body Mass Index (BMI). Data were analyzed by Pearson Product Moment Results:The results showed as many as 63.3% of the subjects with poor nutrition status and the whole subject has less energy and protein intake. Test results showed no correlation bivariate energy intake and nutritional status (p = 0.041) and no correlation with protein intake gizii status (p = 0.185). Conclusion:There is a correlation of energy intake and nutritional status and there is no correlation of protein intake with nutritional status